Zenlens scleral lenses for visual rehabilitation of patients with irregular cornea: a usage experience - O. O. Alyaeva (Российский офтальмологический журнал, 2018)
Scleral lenses improve visual acuity in patients with irregular corneal astigmatism, which is especially important when other methods of correction are ineffective.Purpose: to assess the efficiency of Zenlens scleral lenses in patients with irregular cornea.Material and methods. A total of 120 patients (164 eyes) were examined, including 86 males and 34 females, aged from 13 to 63 years (mean age 35 ± 12 years). The patients were divided into 4 groups. Group 1 consisted of patients with keratoconus, group 2 — postpenetrating keratoplasty, group 3 — keratoconus after cross-linking and/or corneal ring segment implantation, while group 4 consisted of patients with other diseases. The efficiency criteria included visual acuity before and after scleral lens fitting and wearing time (hours per day). To determine social significance of scleral lens wearing, we selected 30 patients (46 eyes) with average best-corrected visual acuity (BCVA) before fitting 0.21 ± 0.08 (0.1–0.3).Results. Average uncorrected visual acuity before fitting did not exceed 0.2 and average visual acuity after fitting was 0.8 ± 0.15. Average improvement in visual acuity after fitting compared to uncorrected visual acuity was at least six lines in all groups and average improvement of visual acuity was approximately three lines compared to BCVA before fitting. 74.4 % and 19.5 % of patients demonstrated long-term (> 10 hours per day) and partial (8–10 hours per day) wear, respectively. Short-term wear (< 8 hours per day) was noted in 6.1 % of patients. Visual acuity of  patients with low BCVA (mean 0.21 ± 0.08) increased by 0.57 (271.4 %).Conclusion. Scleral lenses can be successfully used for visual acuity improvement and social rehabilitation of patients with irregular cornea when other methods of correction are ineffective.